Addressing Contemporary Crime: Implementing the Basic Principles of Islamic Criminal Law - Sabna Anggraini; Sofia Zuhro Zein Pulungan; Ainur Rahma; Asti Nurul Puspita; Rina Solin (Jurnal Sahabat ISNU SU, 2025)
This article examines the application of Islamic criminal law standards in the context of contemporary crime prevention. Islamic criminal law, grounded in ethical and moral values, offers a relevant approach to addressing various forms of contemporary crime, such as cybercrime, fear-based bullying, and insults. This study distinguishes several Islamic criminal law standards, assesses the standards of justice, legal certainty, and practicality, and examines how these standards can be integrated into a positive legal framework to enhance the effectiveness of legal enactment. Furthermore, this article emphasizes the importance of justice and beneficial remedies in dealing with offenders, in order to rebuild disrupted social relationships. Thus, the application of Islamic criminal law standards is expected to provide a comprehensive and relevant regulation in addressing the challenges of modern crime, while still adhering to human rights standards and humanitarian values.